Are histomorphologic changes in the fimbrial ends more to blame for primary epithelial ovarian carcinomas than initially thought - ERBARUT SEVEN, İPEK; ÖZKAN YENAL, NAZİYE (My University, 2022)
Objective: To investigate the relationship between primary epithelial ovarian tumors and histomorphologic changes in the fimbrial ends (FEs) of the fallopian tubes. Materials and Methods: Twenty-eight serous carcinomas (SCs) and 12 non-serous carcinomas (NSC) were studied. Ovarian and concomitant invasive tumors in FEs were labeled with PAX8, WT-1 and Calretinin. Results: Eighty-six percent of SCs were high grade (HG), 14% of were low grade (LG). 71% of SCs (85% HG, 15% LG) had concomitant invasive tumors in FEs. Serous tubal intraepithelial carcinoma (STIC) was seen in 29% (75% HG, 25% LG), all had concomitant invasive tumors in FEs. The presence of tumors in FEs was statistically significant in SCs (p=0.03). 33% of NSCs had concomitantly invasive tumors in FEs. 67% of endometrioid tumors, 33% of clear cell carcinomas had endometriosis. 50% of mucinous tumors, 67% of endometrioid tumors, 50% of benign Brenner tumors had Walthard nest. Except for mucinous carcinomas, ovarian and concomitant invasive tumors in FEs displayed tubal phenotype (Calretinin-/PAX8+). Conclusion: The results of our study suggest that, invasive tumors and STIC in FEs are not only limited to HGSCs, but can also be seen in LGs. FEs could also be a site of origin for NSCs, however, future studies with more cases are needed.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Primary epithelial ovarian tumors; Fallopian tubes; Fimbrial ends; Histomorphologic changes; Early detection; FALLOPIAN-TUBE; SEROUS CARCINOMA; CANCER; PATHOGENESIS; MUTATIONS; ORIGIN; WOMEN; PRECURSORS; TUMORS; SITE; Primary epithelial ovarian tumors; Fallopian tubes; Fimbrial ends; Histomorphologic changes; Early detection